HUBUNGAN ANTARA ROLE EFFICACY DENGAN JOB PERFORMANCE PADA KARYAWAN CV BELANTARA CANTON PARK PALEMBANG - Oktaviana, Rina (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2016)
This study aimed to investigate relationship between role efficacy with job performanc in the employee CV Belantara Canton Park in Palembang. Dependent variable in this study is a job performanc, Role Efficacy an independent variable. This research uses a scale of job performanc and role efficacy. The sample used 40 employee. The results of this research showed a significant relationship between role efficacy with  job performanc in the employee CV Belantara Canton Park in  Palembang with a value of r = 0.796, p = 0.000 for the results of significance (p) 0.000 mean value of p <0.01. So otherwise there is a very significant relationship role efficacy contributes to Job Performanc of 63.4%.